(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article The main social, political and theoretical prerequisites for the emergence and formation of the humanistic tradition in international relations at the end of the twentieth century have been identified . The main “problem nodes” in the field of humanization of international relations have been studied.